Reactions to Feedback: The Role of Attributions - Liden, Robert C.; Mitchell, Terence R. (Academy of Management Journal, 1985)
This study tested reactions to feedback in an experimental simulation. Feedback specificity and information that could be used to make causal inferences were manipulated through varying information on consistency, distinctiveness, and consensus. As predicted, subjects rated specific feedback more positively than they rated nonspecific feedback, and preferred feedback that suggested an external cause of poor performance to feedback that suggested an internal cause. However, the latter was not preferred to nonspecific feedback.